2017
DOI: 10.1021/acs.joc.7b01272
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Sulfur-Containing Organic Compounds and Peptides in 1-Ethyl-3-methyl-imidazolium Acetate

Abstract: The neat ionic liquid (IL) [Cmim][OAc] is not just capable of dissolving thiol- and disulfide-containing compounds, but is able to chemically react with them without addition of any catalytic reagent. Through the analysis of four small organic molecules and a cysteine-containing peptide we could postulate a general reaction mechanism. Here, the imidazolium-carbenes preferentially react with the disulfide bond, but not thiol group. Moreover, the imidazole moiety was found to abstract the sulfur atom from the cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 44 publications
1
30
0
Order By: Relevance
“…It has been recently reported [25] that neat 1-ethyl-3-methyl-imidazolium acetate is able to react with disulfide species to form the same imidazole 2-thione observed by us. The evolution of the reaction was followed by 1 H-NMR and it was proposed that the reaction proceeded through the formation of a carbene, by the abstraction of the H-2 proton from the imidazolium promoted by the acetate, followed by a nucleophilic substitution on the disulfide.…”
Section: Resultssupporting
confidence: 74%
“…It has been recently reported [25] that neat 1-ethyl-3-methyl-imidazolium acetate is able to react with disulfide species to form the same imidazole 2-thione observed by us. The evolution of the reaction was followed by 1 H-NMR and it was proposed that the reaction proceeded through the formation of a carbene, by the abstraction of the H-2 proton from the imidazolium promoted by the acetate, followed by a nucleophilic substitution on the disulfide.…”
Section: Resultssupporting
confidence: 74%
“…However, N-heterocyclic carbenes (NHC) which are present in the neat [C 2 mim][OAc], generated by subtraction of C2 proton by relatively basic acetate anion, initiated formation of a high percentage of by-products and therefore prevented the breakthrough of this method. In 2017, we identified those NHC-induced side-products and studied conditions where the formation of those side-products can be entirely suppressed, therefore enabling using [C 2 mim][OAc] as a solvent during NCL (Baumruck et al, 2017). Additionally, Wehofsky et al (2008) reported protease-catalyzed ligation in the presence of 60% of 3-methylimidazolium dimethylphosphate in buffer solution with high turnover rates.…”
Section: External Conditionsmentioning
confidence: 99%
“…A further promising approach offers ionic liquids as possible media for peptide desulfurization. Studies performed in [C 2 mim][OAc] gave first evidence that Cys can be desulfurized to Ala within the sequence of unprotected peptides (Baumruck et al, 2017). When applying desulfurization conditions, all other present cysteines need to be orthogonally protected.…”
Section: Structurementioning
confidence: 99%
See 1 more Smart Citation
“…The demonstration of the potential presence of NHC in imidazolium acetates was obtained by many groups, carrying out successfully catalyzed or stoichiometric reactions (Lambert et al, 2016; Baumruck et al, 2017; Binks et al, 2018; Pandolfi et al, 2018), but in no case any attempt to evidence the actual presence of NHC was done. This last topic was faced in a few papers.…”
Section: Experimental Studiesmentioning
confidence: 99%